TECHNIKI OBRAZOWANIACritical aortic coarctation – usefulness of multislice computed tomography in preoperative planning and assessing the effect of surgical treatment. Case report of two patients - Głowacki, Jan; Przybylski, Roman; Miszalski-Jamka, Karol; Andrecka-Sikora, Weronika; Wasilewski, Jarosław; Zembala, Marian (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2011)
Coarctation of aorta is one of eight most common congenital heart and great vessels disease. Authors shows the usefulness of multislice computed tomography in diagnosis and choosing the best method of surgical treatment of coarctationon on the base of two cases in young adults.